Repeatedly Northwards and Upwards: Southern African Grasslands Fuel the Colonization of the African Sky Islands in Helichrysum (Compositae) - Blanco-Gavaldà, Carme; Galbany-Casals, Mercè; Susanna, Alfonso; Andrés-Sánchez, Santiago; Bayer, Randall J; Brochmann, Christian; Cron, Glynis V; Bergh, Nicola G; Garcia-Jacas, Núria; Gizaw, Abel; Kandziora, Martha; Kolář, Filip; et al. (Plants (Basel, Switzerland), 2023)
The Afromontane and Afroalpine areas constitute some of the main biodiversity hotspots of Africa. They are particularly rich in plant endemics, but the biogeographic origins and evolutionary processes leading to this outstanding diversity are poorly understood. We performed phylogenomic and biogeographic analyses of one of the most species-rich plant genera in these mountains, Helichrysum (Compositae-Gnaphalieae). Most previous studies have focused on Afroalpine elements of Eurasian origin, and the southern African origin of Helichrysum provides an interesting counterexample. We obtained a comprehensive nuclear dataset from 304 species (≈50% of the genus) using target-enrichment with the Compositae1061 probe set. Summary-coalescent and concatenation approaches combined with paralog recovery yielded congruent, well-resolved phylogenies. Ancestral range estimations revealed that Helichrysum originated in arid southern Africa, whereas the southern African grasslands were the source of most lineages that dispersed within and outside Africa. Colonization of the tropical Afromontane and Afroalpine areas occurred repeatedly throughout the Miocene-Pliocene. This timing coincides with mountain uplift and the onset of glacial cycles, which together may have facilitated both speciation and intermountain gene flow, contributing to the evolution of the Afroalpine flora.
Keywords: Helichrysum; biogeography; Asteraceae; long-distance dispersal; phylogeny; Afromontane; evolution; target-enrichment; Afroalpine